2013
DOI: 10.1096/fj.13-229591
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human lactoferrin induces human and mouse dendritic cell maturationviaToll‐like receptors 2 and 4

Abstract: Lactoferrin, a key component of innate immunity, is a cationic monomeric 80-kDa glycoprotein of the transferrin superfamily. Recombinant human lactoferrin, known as talactoferrin (TLF), induces a distinct functional maturation program in human dendritic cells (DCs) derived from peripheral blood monocytes. However, the receptors and molecular mechanisms involved in this induction have not been fully determined. By exploiting genome-wide transcription profiling of immature DCs, TNF-α- and IL-1β-matured DCs (m-DC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 51 publications
1
17
0
Order By: Relevance
“…This limited data suggest that the CD16 + macrophage may demonstrate changes in LPS induced TLR-4 signaling. Lactoferrin’s mechanism to regulate LPS induced inflammation is thought to occur through the LPS-TLR-4 signaling cascade [5965]. One potential hypothesis for why recombinant human lactoferrin did not affect CD16 + macrophage cytokine/chemokine production maybe due to the innate changes in the LPS-TLR-4 signaling cascade, compared to CD14 + macrophage response.…”
Section: Discussionmentioning
confidence: 99%
“…This limited data suggest that the CD16 + macrophage may demonstrate changes in LPS induced TLR-4 signaling. Lactoferrin’s mechanism to regulate LPS induced inflammation is thought to occur through the LPS-TLR-4 signaling cascade [5965]. One potential hypothesis for why recombinant human lactoferrin did not affect CD16 + macrophage cytokine/chemokine production maybe due to the innate changes in the LPS-TLR-4 signaling cascade, compared to CD14 + macrophage response.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial DCs ( 83 ), keratinocytes ( 84 ), and oral epithelial cells ( 85 ) bear CD14 and TLRs able to recognize LTF. More importantly, LTF can trigger maturation of DCs through TLR2 and TLR4 ( 86 ), with such events known to promote DC migration to adjacent lymph nodes ( 87 ). Orally ingested LTF may also interact with intestinal epithelial cells expressing TLRs ( 88 ).…”
Section: Lactoferrin and General Physiologic Homeostasismentioning
confidence: 99%
“…HLf adheres to the DNA structures released due to chromatin decondensation and spreading exerting its antimicrobial properties ( 119 ). In vitro experiments showed that recombinant hLf is able to induce maturation of antigen-presenting cells such as dendritic cells, thus suggesting that it can represent a link in shaping adaptive immunity ( 120 ). Depending on the external stimulus (pathogens, allergen, tumor antigens, etc.)…”
Section: Lactobacilli and Lf Host Immune System Modulationmentioning
confidence: 99%